Carbon prices for meeting the Paris agreement and their impact on key metals. Issue 2 (April 2020) - Tost, Michael; Hitch, Michael; Lutter, Stephan; Feiel, Susanne; Moser, Peter
Highlights: The paper looks at carbon prices, target-consistent with the Paris agreement and their impact on four key metals and mining companies. The impact would still be within the market driven price variations of recent years for copper and gold. The situation looks different for steel and aluminium and for the companies, where prices and profitability would be significantly impacted. In some cases even the minimum carbon prices used in this study would make mining unprofitable. Abstract: Under the Paris Agreement, nations of this world aim to limit temperature increase to well below 2 °C above pre-industrial levels and to pursue efforts to further limit the increase to 1.5 °C. Putting a price on CO2 emissions has been suggested as one approach to tackling global warming. This paper uses the results of suggested carbon pricing systems in the context of the Paris Agreement that consider biophysical boundary conditions for CO2 emissions. The impact of such carbon pricing is estimated statically for two ores – iron ore and bauxite – and four metals/ alloys – steel, aluminium, copper and gold – at a commodity level and a company level for some of the largest mining companies in the world. The authors conclude that at the commodity level the upper-bound impact of carbon pricing on metal prices would still be within the market driven price variations of recent years for copper and gold. The situation however looks different for steel and aluminium and for the companies, where prices and profitability would be significantly impacted, in some cases even by the minimum carbon prices used in this study, which would make mining unprofitable.